Вплив інформаційного суспільства на формування архівної термінології - Клімчук, Оксана (Видавництво Львівської політехніки, 2014)
The paper deals with archives terminology main definitions. The author considers some changes in terminology system under information society conditions. The article describes such terms as "archives" and "digital archive" and their definitions in Ukrainian and foreign resources.
Keywords: архівна термінологія; архів; електронний архів; зберігання документів; інформаційне суспільство